2022
DOI: 10.1098/rspb.2021.2456
|View full text |Cite
|
Sign up to set email alerts
|

Plants in the UK flower a month earlier under recent warming

Abstract: Global temperatures are rising at an unprecedented rate, but environmental responses are often difficult to recognize and quantify. Long-term observations of plant phenology, the annually recurring sequence of plant developmental stages, can provide sensitive measures of climate change and important information for ecosystem services. Here, we present 419 354 recordings of the first flowering date from 406 plant species in the UK between 1753 and 2019 CE. Community-wide first flowering advanced by almost one m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…However, tracking floral traits over time remains rare, and, in contrast to our results, multiple other studies have suggested an increased investment in selfing in response to climate change and pollinator declines (Cheptou, 2019;Busch et al, 2022) with rarer instances of increased outcrossing (Bishop et al, 2017) Our phenology and anther-stigma distance results are similar to responses across other species and previous work in I. purpurea, respectively. Phenology, measured here as the date of first flower, has repeatedly shown a shift to earlier flowering dates in a number of plant species (Bock et al, 2014;Moore & Lauenroth, 2017;Wolf et al, 2017;Büntgen et al, 2022), and this is also the case in I. purpurea. We found some evidence of directional selection toward earlier flowering within the first wave of flower emergence, particularly at northern latitudes.…”
Section: Discussionmentioning
confidence: 68%
“…However, tracking floral traits over time remains rare, and, in contrast to our results, multiple other studies have suggested an increased investment in selfing in response to climate change and pollinator declines (Cheptou, 2019;Busch et al, 2022) with rarer instances of increased outcrossing (Bishop et al, 2017) Our phenology and anther-stigma distance results are similar to responses across other species and previous work in I. purpurea, respectively. Phenology, measured here as the date of first flower, has repeatedly shown a shift to earlier flowering dates in a number of plant species (Bock et al, 2014;Moore & Lauenroth, 2017;Wolf et al, 2017;Büntgen et al, 2022), and this is also the case in I. purpurea. We found some evidence of directional selection toward earlier flowering within the first wave of flower emergence, particularly at northern latitudes.…”
Section: Discussionmentioning
confidence: 68%
“…Although it is often argued that phenological sensitivity to changing climatic conditions may increase or maintain population abundance, this has rarely been tested [ 53 ]. Our results actually suggest that phenological sensitivity could be an adaptation to the inter-annual variation of weather conditions in order to maintain synchrony with resources, which have been shown to respond to the increase of temperatures by advancing their phenology ([ 26 , 54 ] and references therein). This could explain why less sensitive species had sharper declines than highly sensitive species, and why they could potentially be the most negatively affected in the current context of climate change.…”
Section: Discussionmentioning
confidence: 75%
“…Here, we explored the idea that species that show high plasticity of phenology to inter-annual climate variability have a greater ability to cope with climate change, as this trait will favour a greater synchronization with trophic resources that can be highly plastic (e.g. [ 26 ]), and therefore, it would increase individual fitness. We hypothesize that species with high sensitivity to climate—that is, species more likely to advance their phenology in warmer years but also to delay it in colder years—have experienced more positive or fewer negative abundance trends in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the diversity present in the data set has enabled an assessment of variation in changes among species as well as pollination syndrome, a trait not typically evaluated in evaluations of phenological change. Phenology data with similar temporal depth and taxonomic breadth originating in the United Kingdom have revealed critically important findings regarding differential changes among species (Büntgen et al, 2022).…”
Section: Insights From Unique Volunteer-based Data Setsmentioning
confidence: 99%
“…This historical initiative, explicitly designed to collect phenological data and concurrent, standardized meteorological information for an entire region, was unprecedented for North America at the time. Prior to this analysis, most attempts to study multispecies reactions to climate change using historical records have relied either on single‐site, single‐observer efforts (e.g., Thoreau's records at Concord as summarized by Miller‐Rushing & Primack, 2008) or compilations of observations from diverse individuals working independently (Büntgen et al, 2022). The historical data set is especially suited for pairing with modern data because it has the geographic extent that permits association with modern regional records, and yet was conducted under the auspices of a centralized, standardizing project and persisted long enough to create a robust baseline.…”
Section: Introductionmentioning
confidence: 99%